Anterior Open Bite Closure: A Case Report - Sharma, Deepak; Halwai, Hemant Kumar (Orthodontic Journal of Nepal, 2011)
Anterior open bite is often caused by a downward rotation of the mandible and/or by excessive eruption of the posterior teeth. In such cases, it is difficult to establish absolute anchorage for molar intrusion by traditional orthodontic mechanics. This article reports the successful treatment of a severe skeletal anterior open bite case using titanium screw anchorage. A female patient of 31 years of age had open bite of 7 mm with increased facial height. The mini screws were implanted on both maxilla and the mandible, and an intrusion force was provided with elastic chains for 13 months. After active treatment of 19 months, her upper and lower first molars were intruded by about 3 mm each, and good occlusion was achieved. Her retrognathic chin and convex profiles were improved by an upward rotation of the mandible. Our result suggests that titanium screws are useful for intrusion of molars in anterior open bite cases.